Some aspects of the effects of interactions of phenolic antioxidants with dicumyl peroxide on the properties of crosslinked polyolefins - Kudła, S. (Polimery, 2022)
The results of investigations of the effects of the interactions between dicumyl peroxide (DCP) and one of two phenolic antioxidants (AO) on the properties of crosslinked polymers: PE-LD and ethylene/vinyl acetate copolymer (EVA) were described. The following properties were determined: hot set tests, gel index, oxidation induction time (OIT), tensile strength and tensile strain at break. Absolute values of these parameters were given (Table 1 and 2) as well as percentage values referred to comparative samples which, unlike to the samples investigated, contained DCP + AO systems as physical mixtures - not the products of interactions (Table 3). The following variables were chosen: type of polymer, AO type, molar ration DCP:AO (with constant sum DCP + AO kept) and reaction environment (an air or nitrogen). It was found that the use of post-reaction DCP + AO system, instead of the physical mixture of these components, advantageously influences the thermooxidative stability of crosslinked polymers, both PE-LD and EVA. Estimation of the effect of the investigated interactions occurred in DCP + AO systems on the efficiency of crosslinking process, based on gel index measurement, shows lack of such effect in case of both polymers studied. However, the data concerning hot set tests show this effect on EVA crosslinking exists.